Power System Stability - Eloghene Okedu, Kenneth (IntechOpen, 2019)
The target readers for this book are academics and engineers working in universities, research institutes and industry sectors wishing to enhance their knowledge about power system stability. Readers of this book should gain technical ideas and special experience with detailed information about small signal stability, dynamics, modeling, power oscillations and electrical power infrastructures relating to power system stability. The contents of this book provide many solutions to problems that can be integrated into larger research findings and projects. The book addresses some power system stability studies such as an overview of power systems and stability criteria, applications of the trajectory sensitivity theory to small signal stability, power system small signal stability in grid connected smart park, power system dynamics and modeling. The book also describes some recent developments in power oscillations due to ferroresonance, sub synchronous resonance and effects of climate change in electric power infrastructures.